2016
DOI: 10.1038/hortres.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of Cucumis melo fruit development and ripening

Abstract: Hami melon (Cucumis melo) is the most important melon crop grown in the north-western provinces of China. In order to elucidate the genetic and molecular basis of developmental changes related to size, flesh, sugar and sour content, we performed a transcriptome profiling of its fruit development. Over 155 000 000 clean reads were mapped to MELONOMICS genome, yielding a total of 23 299 expressed genes. Of these, 554 genes were specifically expressed in flowers, and 3260 genes in fruit flesh tissues. The 7892 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 41 publications
8
59
1
Order By: Relevance
“…However, ribonucleic acids were degraded (Figure 1, gel bands corresponding to samples 11, 12 and 13). This is among the most widely used methods for RNA extraction, due to its simplicity and efficiency (RAMCHANDRA; STURM, 2010;CORBACHO et al, 2013;CHEN et al, 2016;ZHANG et al, 2016). However, in our study, the extracted material presented a low A 260 nm/A230 nm ratio, indicating the presence of contaminating polysaccharides or polyphenols in both the green and mature fruits.…”
Section: ) Cetyltrimethylammonium Bromide (Ctab)/ Polyvinylpyrrolidonecontrasting
confidence: 51%
“…However, ribonucleic acids were degraded (Figure 1, gel bands corresponding to samples 11, 12 and 13). This is among the most widely used methods for RNA extraction, due to its simplicity and efficiency (RAMCHANDRA; STURM, 2010;CORBACHO et al, 2013;CHEN et al, 2016;ZHANG et al, 2016). However, in our study, the extracted material presented a low A 260 nm/A230 nm ratio, indicating the presence of contaminating polysaccharides or polyphenols in both the green and mature fruits.…”
Section: ) Cetyltrimethylammonium Bromide (Ctab)/ Polyvinylpyrrolidonecontrasting
confidence: 51%
“…In fruit maturation, there is a gradual expression increase of CmSUS1 and decrease of CmSUS2 in the 'Yellow' melon. In non-climacteric melons, 'Hami' [51] and 'Piel del Sapo' [6], the same expression profile was observed. In 'Dulce' climacteric melon, the CmSUS1 was more expressed in young fruit, followed by near-silencing in mature fruit.…”
Section: Sucrose Metabolismmentioning
confidence: 59%
“…Sugar metabolism is an important pathway related to the sweetness of fruits and it is the most attractive characteristic for consumers [51]. Furthermore, studies have reported that sugars may serve as important signals that modulate a wide range of processes in plant physiology including fruit maturation [39,52,53].…”
Section: Sucrose Metabolismmentioning
confidence: 99%
“…In addition to the extensively enriched pathways in COS and LSW177, some DEGs were found to be involved in carotenoid formation, plant hormone signal transduction, sugar metabolism and cell wall metabolism and might have unique functions in cultivated watermelon during fruit ripening. These metabolic pathways are also important for fruit ripening in melon [20], tomato [21] and orange [19]. These pathways have the ability to create an organized metabolic association that possibly cooperates during fruit ripening in cultivated watermelon.…”
Section: Discussionmentioning
confidence: 99%